Level of knowledge about Hepatitis B, vaccination status and biosafety measures of nursing professionals - Adriana Sierra Assencio Almeida Barbosa; Selma Regina Axcar Salotti; Sônia Maria Usó Ruiz Silva (Universidade de Santa Cruz do Sul, 2017)
Backgound and Objectives: Hepatitis B is an important global public health problems. The contamination can occur in any individual, however, health professionals, especially those in the nursing area, are more exposed. Hepatitis B is an occupational disease whose prevention is accessible, without cost in Brazil and mandatory for all healthcare professionals by vaccination. Thus, the present study aimed to verify the vaccination status of the nursing professionals, and yours knowledge about contamination risks with hepatitis B virus (HVB), as well about the biosafety measures to avoid these risks. Methods: A descriptive and cross-sectional study was carried out in a public hospital in the city of Bauru/SP, with nursing professionals. It was applied a questionnaire, between January to March 2015, containing aspects related to the vaccination status, knowledge about HBV and biosafety. Results: From 107 nursing professionals at the institution, 96 (89.8%) accepted to participate in the study, of them 84.3% were with complete vaccination, 3.2% were incomplete and 12.5% did not know their vaccination status. More than 90.0% knew the ways to avoid HVB transmission and had received information about biosafety and waste disposal, but only 81.2% used personal protective equipment (PPE) in their activities. Conclusion: The results indicate that although the nursing professionals knew how to avoid the HBV contamination, they still remains exposed to a hight risk of, and so is necessary to sensitize and awareness about the importance of adopting safe practices and immunization, leading to a behavior modification. KEYWORDS: Nursing Team. Immunization Coverage. Hepatitis B. Occupational Disease. Exposure to Biological Agents.